A sizing methodology based on Levelized Cost of Supplied and Lost Energy for off-grid rural electrification systems. (April 2016) - Mandelli, Stefano; Brivio, Claudio; Colombo, Emanuela; Merlo, Marco
Abstract: Off-grid renewable systems can play a pivotal role in the process of rural electrification, thus promoting local development. Moreover, scientific literature is increasingly addressing this issue through the concept of sustainability and appropriate technologies. With regards to this topic, we present a sizing methodology which better relates the results and the sizing process itself to the local context. Specifically, we address the research area of sizing methodologies for off-grid PV systems. Typically, the Loss of Load Probability (LLP) is a key parameter in these methodologies, but is difficult to set as regards the specific context. The proposed methodology employs the concept of Levelized Cost of Supplied and Lost Energy, it is based on the estimate of an economic Value of Lost Load, and eventually, the LLP results to be an output of the process. Therefore, the methodology uses only data characterizing the local situation and results better fit with population conditions. We also propose a simple approach to compute the Value of Lost Load and we apply the methodology for a rural area of Uganda. The results show that the methodology identifies a reliable system which supplies electricity with a fair cost while minimizing the energy bill of the consumers. Highlights: We address the issue of sizing off-grid power systems for rural areas. We modify the definition of Net Present Cost for energy systems. We develop the concept of Levelized Cost of Supplied and Lost Energy. We apply the new objective function to design an off-grid PV system in rural Uganda.